From bycatch to litter: a systematic map of the ecological impacts of fishing in European seas - Esther D. Beukhof; Sven Sebastian Uhlmann; Karin J. van der Reijden; Aikaterini Anastasopoulou; Miren Altuna-Etxabe; Amaia Astarloa; Oihane C. Basurko; Logan Binch; Joanna K. Bluemel; Pierluigi Carbonara; Grete E. Dinesen; Ole R. Eigaard; et al. (Reviews in Fish Biology and Fisheries, 2026)

Platinum-group element systematics in the North Atlantic Igneous Province: New insights from Northern Irish and Irish magmatism - Anna O. Morrison; Michael J. Stock; Mark R. Cooper; Jens C.Ø. Andersen; Hannah S.R. Hughes; Elliot J. Carter; Jack Beckwith; Iain McDonald; Andrew C. Kerr; Paul Mohr (Lithos, 2026)

121 Extended incubation induces equine sperm hyperactivation and tyrosine phosphorylation as potential predictors of vitro fertilization success - R.A. Gonzalez-Castro; C. Porflidt; A.L. Ash; C. Elliot; E.M. Carnevale (Journal of Equine Veterinary Science, 2026)

Vitamin E acetate and its aerosol activate aryl hydrocarbon receptor signaling and exacerbate inflammation in human U937-derived macrophages - Xiaohan Li; Andrea Rossi; Thomas Haarmann-Stemmann; Elliot R. Spindel; Jack C. Connolly; Allison K. Ehrlich; Kent E. Pinkerton; Christoph F.A. Vogel (Toxicology in Vitro, 2026)

Leveraging national forest inventory data to estimate forest carbon density status and trends for small areas - Elliot S. Shannon; Andrew O. Finley; Paul B. May; Grant M. Domke; Hans-Erik Andersen; George C. Gaines III; Arne Nothdurft; Sudipto Banerjee (Forest Ecology and Management, 2025)

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

Widespread presence of potato virus Y in the main potato-producing region of Paraguay - Diana C. Zorrilla; Marcelo Alborno-Jover; Yerutí Mongelos-Franco; Blanca Coronel; Heron Kraide; Lino Ramirez-Ayala; Adans Colman; Jorge A. M. Rezende; Elliot W. Kitajima; Alfredo Gryciuk Almeida; Arnaldo Esquivel-Fariña (Journal of Plant Pathology, 2025)

Reduced farming density of New Zealand flat oyster Ostrea chilensis is associated with decreased infection by Bonamia ostreae and other parasites - Zoë Hilton; Anne Rolton; Farhana Muznebin; Stephen C. Webb; Andrew Fidler; Andrew Elliot; Javier Atalah; Andrea C. Alfaro; Kate S. Hutson (Aquaculture, 2025)

Insect-parasitic fungi as a model system to investigate coinfections - Eduardo C. Costantin; José A. Roxinol; Pablo F. Braga; Simon Luke Elliot (Journal of Invertebrate Pathology, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Ocean crustal veins record dynamic interplay between plate-cooling-induced cracking and ocean chemistry - Aled D. Evans; Rosalind M. Coggon; Michelle Harris; Elliot J. Carter; Elmar Albers; Gilles M. Guérin; Thomas M. Belgrano; Mallika Jonnalagadda; Lewis J.C. Grant; Pamela D. Kempton; David J. Sanderson; James A. Milton; et al. (Earth and Planetary Science Letters, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cordyceps cateniannulata: An endophyte of coffee, a parasite of coffee leaf rust and a pathogen of coffee pests - Caio M. Pereira; Keminy R. Bautz; María del Carmen H. Rodríguez; Laura M. Saavedra-Tobar; Miraine Kapeua-Ndacnou; Kifle Belachew-Bekele; Simon L. Elliot; Harry C. Evans; Robert W. Barreto (Fungal Biology, 2024)

Soil Black Carbon Increases Under Urban Trees with Road Density and Time: Opportunity Hotspots for Carbon Storage in Urban Ecosystems - Katherina A. Kang; Erika Marín-Spiotta; Elliot Vaughan; C. Reid Ferring; Alexandra G. Ponette-González (Environmental Management, 2024)

Climate change and plant-microbe interactions: Water-availability influences the effective specialization of a fungal pathogen - Jakob Joachin; Camryn Kritzell; Elliot Lagueux; Noah C. Luecke; Kerri M. Crawford (Fungal Ecology, 2023)

Costs of preventing and supressing wildfires in Victoria, Australia - Erica Marshall; Shona Elliot-Kerr; Sarah C. McColl-Gausden; Trent D. Penman (Journal of Environmental Management, 2023)

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

Effects of prebiotics, probiotics, and synbiotics on the infant gut microbiota and other health outcomes: A systematic review - Lynn E. Ferro; Liana N. Crowley; Kyle Bittinger; Elliot S. Friedman; Jessica E. Decker; Kathryn Russel; Sarah Katz; Jae Kyeom Kim; Jillian C. Trabulsi (Critical Reviews in Food Science and Nutrition, 2023)

Nutrient and stoichiometric time series measurements of decomposing coarse detritus in freshwaters - Caleb J. Robbins; Beth C. Norman; Halvor M. Halvorson; David W. P. Manning; Elliot Bastias; Cristiane Biasi; Allyn K. Dodd; Rebecca A. Eckert; Alice Gossiaux; Jérémy Jabiol; Andrew S. Mehring; Ada Pastor (Ecology, 2023)
Decomposition of coarse detritus (e.g., dead organic matter larger than ~1 mm such as leaf litter or animal carcasses) in freshwater ecosystems is well described in terms of mass loss, particularly as rates that compress mass loss into one number (e.g., a first‐order decay coefficient, or breakdown rate, “ k ”); less described are temporal changes in the elemental composition of these materials during decomposition, with important implications for elemental cycling from microbes to ecosystems. This stands in contrast with work in the terrestrial realm, where a focus on detrital elemental cycling has provided a sharper mechanistic understanding of decomposition, especially with specific processes such as immobilization and mineralization. Notably, freshwater ecologists often measure carbon (C), nitrogen (N), and phosphorus (P), and their stoichiometric ratios in decomposing coarse materials, including carcasses, wood, leaf litter, and more, but these measurements remain piecemeal. These detrital nutrients are measurements of the entire detrital–microbial complex and are integrative of numerous processes, especially nutrient immobilization and mineralization, and associated microbial growth and death. Thus, data relevant to an elemental, mechanistically focused decomposition ecology are available in freshwaters, but have not been fully applied to that purpose. We synthesized published detrital nutrient and stoichiometry measurements at a global scale, yielding 4038 observations comprising 810 decomposition time series (i.e., measurements within a defined cohort of decomposing material through time) to build a basis for understanding the temporality of elemental content in freshwater detritus. Specifically, the dataset focuses on temporally and ontogenetically (mass loss) explicit measurements of N, P, and stoichiometry (C:N, C:P, N:P). We also collected ancillary data, including detrital characteristics (e.g., species, lignin content), water physiochemistry, geographic location, incubation system type, and methodological variables (e.g., bag mesh size). These measurements are important to unlocking mechanistic insights into detrital ontogeny (the temporal trajectory of decomposing materials) that can provide a deeper understanding of heterotroph‐driven C and nutrient cycling in freshwaters. Moreover, these data can help to bridge aquatic and terrestrial decomposition ecology, across plant or animal origin. By focusing on temporal trajectories of elements, this dataset facilitates cross‐ecosystem comparisons of fundamental decomposition controls on elemental fluxes. It provides a strong starting point (e.g., via modeling efforts) for comparing processes such as immobilization and mineralization that are understudied in freshwaters. Time series from decomposing leaf litter, particularly in streams, are common in the dataset, but we also synthesized ontogenies of animal‐based detritus, which tend to decompose rapidly compared with plant‐based detritus that contains high concentrations of structural compounds such as lignin and cellulose. Although animal‐based data were rare, comprising only three time series, their inclusion in this dataset underscores the opportunities to develop an understanding of decomposition that encompasses all detrital types, from carrion to leaf litter. There are no copyright or proprietary restrictions on the dataset; please cite this data paper when reusing these materials.

Nutrient and stoichiometry dynamics of decomposing litter in stream ecosystems: A global synthesis - Caleb J. Robbins; David W. P. Manning; Halvor M. Halvorson; Beth C. Norman; Rebecca A. Eckert; Ada Pastor; Allyn K. Dodd; Jérémy Jabiol; Elliot Bastias; Alice Gossiaux; Andrew S. Mehring (Ecology, 2023)
Decomposing organic matter forms a substantial resource base, fueling the biogeochemical function and secondary production of most aquatic ecosystems. However, detrital N (nitrogen) and P (phosphorus) dynamics remain relatively unexplored in aquatic ecosystems relative to terrestrial ecosystems, despite fundamentally linking microbial processes to ecosystem function across broad spatial scales. We synthesized 217 published time series of detrital carbon (C), N, P, and their stoichiometric ratios (C:N, C:P, N:P) from stream ecosystems to analyze the temporal nutrient dynamics of decomposing litter using generalized additive models. Model results indicated that detritus was a net source of N (irrespective of inorganic or organic form) to the environment, regardless of initial N content. In contrast, P sink/source dynamics were more strongly influenced by the initial P content, in which P‐poor litters were sinks for nutrients until these shifted to net P mineralization after ~40% mass loss. However, large variations surrounded both the N and P predictions, suggesting the importance of nonmicrobial factors such as fragmentation by invertebrates. Detrital C:N ratios converged and became more similar toward the end of the decomposition, suggesting predictable microbial functional effects throughout detrital ontogeny. C:P and N:P ratios also converged to some degree, but these model predictions were less robust than for C:N, due in part to the lower number of published detrital C:P time series. The explorations of environmental covariate effects were frequently limited by a few coincident covariate measurements across studies, but temperature, N availability, and P tended to accelerate the existing ontogenetic patterns in C:N. Our analysis helps to unite organic matter decomposition across aquatic–terrestrial boundaries by describing the basic patterns of elemental flows catalyzed by decomposition in streams, and points to a research agenda with which to continue addressing gaps in our knowledge of detrital nutrient dynamics across ecosystems.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Transgenerational transfer of the microbiome is altered by ocean acidification in oyster larvae - Elliot Scanes; Pauline M. Ross; Justin R. Seymour; Nachshon Siboni; Michael C. Dove; Wayne A. O'Connor; Callum Dittes; Laura M. Parker (Aquaculture, 2023)

Effect of High-Intensity Intermittent Hypoxic Training on 3-on-3 Female Basketball Player’s Performance - H. K. Smith; M. J. Hamlin; C. A. Elliot (Journal of Science in Sport and Exercise, 2022)
Purpose To investigate the effects of 4 weeks high-intensity interval training in hypoxia on aerobic and anaerobic performance of 3-on-3 basketball players. Methods In a randomised controlled trial, 15 female basketballers completed eight 1-h high-intensity training sessions in either normobaric hypoxia (hypoxic group n = 8, altitude 3052 m) or normoxia (normoxic group n = 7, sea-level). Results After training, the hypoxic group increased their 1-min all-out shuttle run distance by 2.5% ± 2.3% (mean ± 95% CI, d = 0.83, P = 0.04), compared to the normoxic group 0.2% ± 2.3% ( d = 0.06, P = 0.8), with the difference between groups being clinically worthwhile but not statistically significant ( d = 0.77, P = 0.1). Distance covered in the Yo-Yo intermittent recovery test tended to increase in the hypoxic (32.5% ± 39.3%, d = 1.0, P = 0.1) but not normoxic group (0.3% ± 24.5%, d = 0.08, P = 0.9), with a non-significant change between groups ( d = 0.9, P = 0.2). Compared to normoxia, the hypoxic group significantly increased subjective markers of stress ( d = 0.53, P = 0.005), fatigue ( d = 0.43, P = 0.005), and muscle soreness ( d = 0.46, P = 0.01), which resulted in a lower perceived training performance in the hypoxic compared to the normoxic group ( d = 0.68, P = 0.001). Conclusion High-intensity interval training under hypoxic conditions likely improved 1-min all-out shuttle run ability in female basketball 3-on-3 players but also increased subjective markers of stress and fatigue which must be taken into consideration when prescribing such training.

The distribution of mycosporine-like amino acids in phytoplankton across a Southern Ocean transect - Elliot L. Weiss; Mattias Rolf Cape; B. Jack Pan; Maria Vernet; Chase C. James; Tim J. Smyth; Sun-Yong Ha; José L. Iriarte; B. Greg Mitchell (Frontiers in Marine Science, 2022)
Interactions between phytoplankton and ultraviolet radiation (UVR: 280 – 400 nm) are undergoing changes dictated by variability in ocean temperature, the depth of mixed layers, nutrient availability, and the thickness of the ozone layer. There are a variety of mechanisms for phytoplankton to cope with UVR stress, one of the most prevalent being the presence of mycosporine-like amino acids (MAAs). Despite the importance of these molecules to phytoplankton fitness under UVR stress, knowledge of the diversity and distribution of these molecules in the world’s oceans is relatively limited. Here, the composition and distribution of MAAs in phytoplankton were examined in a transect across the Southern Ocean, crossing multiple fronts, from eastern New Zealand to the West Antarctic Peninsula in March and April of 2018. The highest concentration of MAAs (> 0.2 μg/L) was found between 50 and 60°S, as well as along a longitudinal gradient between 137.47 and 144.78°W. A strong correlation was found between a model of the preceding month’s UVR dosage experienced in the mixed layer and the ratio of MAAs to chlorophyll-a across the transect, indicating a relationship between the integrated history of light exposure and phytoplankton physiology. Haptophytes accounted for the majority of biomass north of the polar front (PF) and were strongly correlated with a diversity of MAAs. South of the PF a transition to a community dominated by diatoms was observed, with community composition changes strongly correlated to porphyra-334 concentrations. The data presented here provide a baseline for MAA abundance and association with specific phytoplankton taxa across the Southern Ocean amid a changing climate.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global biogeographic patterns of avian morphological diversity - Emma C. Hughes; David P. Edwards; Jen A. Bright; Elliot J.R. Capp; Christopher R. Cooney; Zoë K. Varley; Gavin H. Thomas (Ecology Letters, 2022)
Understanding the biogeographical patterns, and evolutionary and environmental drivers, underpinning morphological diversity are key for determining its origins and conservation. Using a comprehensive set of continuous morphological traits extracted from museum collections of 8353 bird species, including geometric morphometric beak shape data, we find that avian morphological diversity is unevenly distributed globally, even after controlling for species richness, with exceptionally dense packing of species in hyper‐diverse tropical hotspots. At the regional level, these areas also have high morphological variance, with species exhibiting high phenotypic diversity. Evolutionary history likely plays a key role in shaping these patterns, with evolutionarily old species contributing to niche expansion, and young species contributing to niche packing. Taken together, these results imply that the tropics are both ‘cradles’ and ‘museums’ of phenotypic diversity.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A predatory mite as potential biological control agent of Diaphorina citri - Milena O. Kalile; André C. Cardoso; Angelo Pallini; Morgana M. Fonseca; Simon L. Elliot; Verônica S. Fialho; Tércio da S. Carvalho; Arne Janssen (BioControl, 2021)

Explaining the worldwide distributions of two highly mobile species: Cakile edentula and Cakile maritima - Elliot C. Shaw; Rachael Fowler; Sara Ohadi; Michael J. Bayly; Rosemary A. Barrett; Josquin Tibbits; Allan Strand; Charles G. Willis; Kathleen Donohue; Philipp Robeck; Roger D. Cousens (Journal of Biogeography, 2021)
Aim If we are able to determine the geographic origin of an invasion, as well as its known area of introduction, we can better appreciate the innate environmental tolerance of a species and the strength of selection for adaptation that colonizing populations have undergone. It also enables us to maximize the success of searches for effective biological control agents. We determined the number of successful colonization events that have occurred throughout the world for two Cakile species and compared the climates from which they originated, in which they established and then spread. Location Worldwide. Taxon Sea‐Rockets ( Cakile spp.), Brassicaceae. Methods We used a high‐throughput sequencing and a genome skimming approach combined with Bayesian Inference phylogenetics to examine variation in entire chloroplast genomes and regions of nuclear ribosomal DNA within native and introduced areas. Databases were used to compare climates between native ranges and introduced regions for multiple clades within each species. Results At least seven clades have invaded different regions of the world. In most cases we were able to identify their source regions and climates. The environmental bottlenecks differed in intensity: while some clades colonized into climates that were similar to climates in their native range, other clades had a very broad innate environmental tolerance such that new invasions succeeded beyond the climate range of native populations. We found clear evidence of hybridization—specifically, chloroplast capture—between two species in Australia. Conclusions Results here show that these species are sometimes capable of colonizing in climates that are beyond the climate range of native populations. Whether successful colonization beyond native climate niches requires de novo adaptation, or whether it represents an innate broad fundamental niche requires further investigation. Cakile species provide an excellent opportunity to study replicated climate adaptation trajectories.

Potential of tropical macroalgae from French Polynesia for biotechnological applications - Mayalen Zubia; Olivier P. Thomas; Stéphanie Soulet; Marina Demoy-Schneider; Denis Saulnier; Solène Connan; Elliot C. Murphy; Florent Tintillier; Valérie Stiger-Pouvreau; Sylvain Petek (Journal of Applied Phycology, 2020)

Coenzyme Q10 Alleviates Chronic Nucleoside Reverse Transcriptase Inhibitor-Induced Premature Endothelial Senescence - Yi-Fan Chen; Valeria Y. Hebert; Krisztian Stadler; Stephen Y. Xue; Kate Slaybaugh; Elliot Luttrell-Williams; Mitzi C. Glover; David M. Krzywanski; Tammy R. Dugas (Cardiovascular Toxicology, 2019)

A resting state fMRI analysis pipeline for pooling inference across diverse cohorts: an ENIGMA rs-fMRI protocol - Bhim M. Adhikari; Neda Jahanshad; Dinesh Shukla; Jessica Turner; Dominik Grotegerd; Udo Dannlowski; Harald Kugel; Jennifer Engelen; Bruno Dietsche; Axel Krug; Tilo Kircher; Els Fieremans; et al. (Brain Imaging and Behavior, 2019)

Identification of a novel species of Eimeria Schneider, 1875 from the woylie, Bettongia penicillata Gray (Diprotodontia: Potoroidae) and the genetic characterisation of three Eimeria spp. from other potoroid marsupials - Amy S. Northover; Sarah Keatley; Aileen D. Elliot; Russell P. Hobbs; Rongchang Yang; Alan J. Lymbery; Stephanie S. Godfrey; Adrian F. Wayne; R. C. Andrew Thompson (Systematic Parasitology, 2019)

Evacuation of multiple magma bodies and the onset of caldera collapse in a supereruption, captured in glass and mineral compositions - Elliot J. Swallow; Colin J. N. Wilson; Madison L. Myers; Paul J. Wallace; Katie S. Collins; Euan G. C. Smith (Contributions to Mineralogy and Petrology, 2018)

Risk and protective factors for structural brain ageing in the eighth decade of life - Stuart J. Ritchie; Elliot M. Tucker-Drob; Simon R. Cox; David Alexander Dickie; Maria del C. Valdés Hernández; Janie Corley; Natalie A. Royle; Paul Redmond; Susana Muñoz Maniega; Alison Pattie; Benjamin S. Aribisala; Adele M. Taylor; et al. (Brain Structure and Function, 2017)

Virus-vector relationship in the Citrus leprosis pathosystem - Aline Daniele Tassi; Laura Cristina Garita-Salazar; Lilian Amorim; Valdenice Moreira Novelli; Juliana Freitas-Astúa; Carl C. Childers; Elliot W. Kitajima (Experimental and Applied Acarology, 2017)

Biological and molecular characterization of a putative new potexvirus infecting Senna occidentalis - Jorge A. M. Rezende; Viviana M. Camelo-García; Sónia C. S. Andrade; José E. Buriolla; Elliot W. Kitajima; Ligia M. L. Duarte (Archives of Virology, 2017)

Using detailed monitoring data to simulate spatial sediment loading in a watershed - Rajith Mukundan; Donald C. Pierson; Elliot M. Schneiderman; Mark S. Zion (Environmental Monitoring and Assessment, 2015)

Quality control by leaf-cutting ants: evidence from communities of endophytic fungi in foraged and rejected vegetation - Silma L. Rocha; Vanessa L. Jorge; Terezinha M. C. Della Lucia; Robert W. Barreto; Harry C. Evans; Simon L. Elliot (Arthropod-Plant Interactions, 2014)

Gene flow and immigration: genetic diversity and population structure of lions (Panthera leo) in Hwange National Park, Zimbabwe - C. Morandin; A. J. Loveridge; G. Segelbacher; N. Elliot; H. Madzikanda; D. W. Macdonald; J. Höglund (Conservation Genetics, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Effects of Parkinson’s disease on optic flow perception for heading direction during navigation - Cheng-Chieh Lin; Robert C. Wagenaar; Daniel Young; Elliot L. Saltzman; Xiaolin Ren; Sandy Neargarder; Alice Cronin-Golomb (Experimental Brain Research, 2014)

Central venous catheter-related blood stream infections in patients receiving intravenous iloprost for pulmonary hypertension - D. Sammut; C. A. Elliot; D. G. Kiely; I. J. Armstrong; L. Martin; J. Wilkinson; P. Sephton; J. Jones; N. Hamilton; J. Hurdman; E. McLellan; I. Sabroe; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Effect of resinous extract from Commiphora swynnertonii (Burrt) on experimental coccidial infection in chickens - Gaymary G. Bakari; Robert A. Max; Robinson H. Mdegela; Elliot C. J. Phiri; Mkumbukwa M. A. Mtambo (Tropical Animal Health and Production, 2013)

Investigating the impact of climate change on New York City’s primary water supply - Adão H. Matonse; Donald C. Pierson; Allan Frei; Mark S. Zion; Aavudai Anandhi; Elliot Schneiderman; Ben Wright (Climatic Change, 2013)

Characterization of a novel tymovirus on tomato plants in Brazil - Virgínia Carla de Oliveira; Tatsuya Nagata; Felipe C. Guimarães; Fernanda A. Ferreira; Elliot Watanabe Kitajima; Cícero Nicolini; Renato de Oliveira Resende; Alice Kazuko Inoue-Nagata (Virus Genes, 2013)

Antiviral activity of crude extracts from Commiphora swynnertonii against Newcastle disease virus in ovo - Gaymary George Bakari; Robert A. Max; Robinson H. Mdegela; Elliot C. J. Phiri; Mkumbukwa M. A. Mtambo (Tropical Animal Health and Production, 2012)

Erratum to: Role of CD73 and extracellular adenosine in disease - Elliot Tapper; Moritz Schmelzle; Holger K. Eltzschig; Simon C. Robson (Purinergic Signalling, 2012)

Effect of sorbitol concentration on regeneration of embryogenic calli in upland rice varieties (Oryza sativa L.) - Pengpeng Geng; Honggui La; Huaqi Wang; Elliot J. C. Stevens (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

An eddy covariance mesonet to measure the effect of forest age on land–atmosphere exchange - MICHAEL L. GOULDEN; GREGORY C. WINSTON; ANDREW M. S. McMILLAN; MARCY E. LITVAK; EDWARD L. READ; ADRIAN V. ROCHA; J. ROB ELLIOT (Global Change Biology, 2006)
We deployed a mesonet of year‐round eddy covariance towers in boreal forest stands that last burned in ∼1850, ∼1930, 1964, 1981, 1989, 1998, and 2003 to understand how CO 2 exchange and evapotranspiration change during secondary succession. We used MODIS imagery to establish that the tower sites were representative of the patterns of secondary succession in the region, and Landsat images to show that the individual stands have changed over the last 22 years in ways that match the spatially derived trends. The eddy covariance towers were well matched, with similar equipment and programs, which maximized site‐to‐site precision and allowed us to operate the network in an efficient manner. The six oldest sites were fully operational for ∼90% of the growing season and ∼70% of the dormant season from 2001 or 2002 to 2004, with most of the missing data caused by low battery charge or bad signals from the sonic anemometers. The rates of midday growing‐season CO 2 uptake recovered to preburn levels within 4 years of fire. The seasonality of land–atmosphere exchange and growing‐season length changed markedly with stand age. The foliage in the younger stands (1989, 1998, and 2003 burns) was almost entirely deciduous, which resulted in comparatively short growing seasons that lasted ∼65 days. In contrast, the older stands (1850, 1930, 1964, and 1981) were mostly evergreen, which resulted in comparatively long growing seasons that lasted ∼130 days. The eddy covariance mesonet approach we describe could be used within the context of other ecological experimental designs such as controlled manipulations and gradient comparisons.

Fed-batch two-phase production of alanine by a metabolically engineered Escherichia coli - Geoffrey M. Smith; Sarah A. Lee; Kevin C. Reilly; Mark A. Eiteman; Elliot Altman (Biotechnology Letters, 2006)

Biomechanical mechanism for transitions in phase and frequency of arm and leg swing during walking - Masayoshi Kubo; Robert C. Wagenaar; Elliot Saltzman; Kenneth G. Holt (Biological Cybernetics, 2004)

INTERACTIONS BETWEEN KILLER WHALES ( ORCINUS ORCA ) AND SPERM WHALES ( PHYSETER MACROCEPHALUS ) WITH A LONGLINE FISHING VESSEL - C. P. Nolan; G. M. Liddle; J. Elliot (Marine Mammal Science, 2000)

An edited linkage map for the AXB and BXA recombinant inbred mouse strains - Stephen B. Sampson; David C. Higgins; Rosemary W. Elliot; Benjamin A. Taylor; Kira K. Lueders; Robert A. Koza; Beverly Paigen (Mammalian Genome, 1998)